Representation Of Woman Leader In The Qur'an (Power-Knowledge Relations In The Discourse On Surah An-Naml 20-44) - Fathiyaturrahmah, Fathiyaturrahmah; Wibowo, Safrudin Edi; Ibrahim Zaghloul, Taha Ramadan (Jurnal Ushuluddin, 2024)
The presentation of the story of Queen Bilqis in the Qur’an has sparked debate among Muslim scholars regarding women's public leadership. The majority of classical and modern scholars argue that the positive portrayal of Bilqis in the Qur’an cannot be used as evidence of women’s suitability for leadership roles, as this tradition is associated with non-believers. Only a few scholars use the positive image of Bilqis as an argument for women’s leadership capabilities, asserting that it is inconceivable for the Qur’an to depict something forbidden in a positive light. This study aims to reveal the Qur’anic ideology on women’s leadership, the pro and con responses of scholars to this ideology, and the factors that have led to the dominance of interpretations that prohibit women’s leadership. This research is a literature review with a feminist approach. Data were collected through bibliographic searches of Qur’anic exegesis from the classical to the modern era. The study shows that the Qur’an fully and unconditionally recognizes women’s public leadership. However, this gender-egalitarian Qur’anic ideology has not developed from the classical to the modern era due to power-knowledge relations that regulate, limit, and control the discourse surrounding women’s agency in the Islamic public sphere. The study recommends providing equal access to women in public leadership spaces